Environmental and Social Management System Toolkit - International Finance Corporation (Washington, DC, 2017)
Environmental and social responsibility is becoming more and more important in today’s global economy. There are thousands of environmental and social codes and standards in the world today. The codes and standards define the rules and the objectives. An environmental and social management system helps companies to integrate the rules and objectives into core business operations through a set of clearly defined, repeatable processes. The authors provide tools to build or enhance the company’s environmental and social management system (ESMS), such as sample documents, blank forms, flowcharts, checklists, and templates. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.